ANTIHYPERTENSIVE EFFICACY OF OLMESARTAN MEDOXOMIL, A NEW ANGIOTENSIN II RECEPTOR ANTAGONIST, AS ASSESSED BY AMBULATORY BLOOD PRESSURE MEASUREMENTS - J. M. Neutel; W. J. Elliott; J. L. Izzo; C. L. Chen; H. N. Masonson (Российский кардиологический журнал)
Olmesartan medoxomil is a new angiotensin II receptor blocker. In this randomized, double-blind, placebo-controlled study, the efficacy and safety of olmesartan medoxomil was assessed in 334 patients with moderate to severe essential hypertension. Patients were randomized to receive placebo; 5, 20, or 80 mg olmesartan medoxomil q.d.; or 2,5, 10, or 40 mg olmesartan medoxomil b.i.d. Ambulatory and cuff blood pressure were measured prior to and after 8 weeks of treatment. Treatment with olmesartan medoxomil resulted in a significant placebo-adjusted reduction of mean 24-hour ambulatory diastolic blood pressure of 9,6 mm Hg, 12,2 mm Hg, and 10,6 mm Hg in the 5-, 20-, and 80-mg q.d. groups, respectively. Corresponding reductions in mean ambulatory systolic blood pressure were 14,5 mm Hg, 16,5 mm Hg, and 15,4 mm Hg. Similar reductions of diastolic and systolic blood pressure were seen with b.i.d. dosing. The diastolic trough-to-peak ratios of the q.d. doses of olmesartan medoxomil ranged from 57% to 70%, indicating 24-hour effectiveness. The safety profile of olmesartan medoxomil was similar to that of placebo. Olmesartan medoxomil appears to be a safe and effective once-a-day treatment for hypertension.